OPTIMIZATION OF ACECLOFENAC ONCE DAILY MATRIX TABLETS: IN-VITRO AND IN-VIVO STUDIES - Shoukri R A, Mohsen A*, Khoweysa O M (Journal of Pharmaceutical Research and Opinion, 2014)
Aceclofenac is a non-steroidal anti-inflammatory drug (NSAID) indicated for symptomatic treatment of pain and inflammation. The short biological half-life (4 h) and dosing frequency make aceclofenac a suitable candidate for sustained release formulations. Sustained release matrix tablets of aceclofenac with Eudragit® RSPO and Eudragit® RLPO were prepared using three techniques; direct compression, wet granulation and solid dispersion. The most optimum matrix formula was manipulated by addition of an immediate release layer for prompt release of the drug. All tablets were evaluated regarding their physical properties and in-vitro release over 24 hours. All the tablets were found within the permissible limits for various physical parameters. In-vitro release studies revealed that Eudragit RSPO retarded the release more than Eudragit RLPO and solid dispersion was the most suitable preparation technique. Formulation F5 was selected for further optimization by addition of fast release layer. The double layer tablet (F19) was successful in prolonging drug release up to 24 hours. Pharmacokinetic studies in albino rabbits were conducted for the optimized formula (Registration No. PI-260). The results of pharmacokinetic studies showed that F19 exhibited longer MRT when compared to the commercial brand of aceclofenac immediate release tablet (Bristaflam®), demonstrating the sustained release properties of F19.